Analysis and Determination of Idler Spacing of Pipe Belt Conveyor - Qiu Shengdong; Chen Jianneng (Jixie chuandong)
The roller is a crucial component with regard to pipe belt conveyor system,which supports belts and cargos,reducing the number of roller can effectively reduce the production cost. Aiming at the pipe belt conveyor roller pitch design and layout issues,taking the typical positive six sides shaped roller group structure as an example,the mechanical analysis and deduction are conducted by considering the interaction relation between the conveyor belt,material and roller structure. The four main factors that affect the spacing between rollers are expounded. Moreover,the mathematical expression of reasonable arrangement of roller spacing is derived,and the correctness of the expression is verified by an engineering example. The results can take the reference for accurate quantitative analysis and optimal design and pipe belt conveyor.